Aspects of Myth in the Homeric Hymn to Hermes - Jarczyk, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The article explores the narrative recounted in the Homeric Hymn to Hermes for its aetiological and educational content and message. In particular, it discusses the creation of the lyre, the role of music in paideia and a less explored view of the protagonist’s cattle raid as it relates to war, sports and the education of youth. It then explores the religious context and specific meaning of Hermes slaughtering two of the stolen cows by contrasting his actions with those of Prometheus.